An interactive wildlife development framework for 3D racing game - Tng, John Cheun Hou (2009)
This thesis describes the development and framework of an interactive wildlife system for the next generation of highly interactive computer games. Current games have racing themes that include animated animals which are non-interactive. This means that animals in these games do not react to a player’s action. For example, players in such games cannot pursue an animal. This wildlife system creates interactive animals for racing games where players can observe animals’ behaviour through high resolution animations, hear sounds they produced or chase them around. This is a new kind of game play experience that has not been implemented before. Interactivity with the animals lets players feel that these animals are part of the game and not merely decorations. This enhances the realism of the game and makes the game more interesting. This wildlife system shows that with the use of graphics hardware and optimisation techniques, it is possible to implement a cost and resource efficient interactive and realistic wildlife system for 3D racing games.